Cumulative impact of herbicides and tillage in conservation agriculture on soil microbiome, fungal diversity and crop productivity - Knight Nthebere; Ram Prakash Tata; Padmaja Bhimireddy; Latha P. Chandran; Jayasree Gudapati; Manikyala Bhargava Narasimha Yadav; Nishant Kumar Sinha; Meena Admala (Scientific Reports)
Abstract Conservation agriculture experiment was undertaken to investigate synergistic effects of tillage and weed management on soil microbiome, and fungal diversity at vegetative (30 DAS) and tasselling (60 DAS) of maize and monitor yield. Main-treatments included T 1 : Conventional tillage (CT) with Cotton- CT with maize- fallow, T 2 : CT with Cotton- Zero tillage (ZT) with Maize- ZT with Sesbania rostrata (Sr) and T 3 : ZT with Cotton + Sr residues- ZT with Maize + Cotton residues- ZT with Sr + Maize stubbles. Weed management (Sub-plots) were W 1 : Chemical weed control, W 2 : Herbicide rotation, W 3 : Integrated weed management (IWM) and W 4 : Single hand-weeded. Rhizo-sphere and plane samples were collected at 30 and 60 DAS for enzymatic, microbial analysis. The results demonstrated 25.90-44.72% and 20.31–50.72% decline on microbial and enzyme activities in T1 + W1, and in T2 + W2, respectively compared to T3 and W4 combinations at 30 DAS, due to herbicidal impact, which increased by 24.67–68.41% and 20.71–62.90% at tasseling. Metabolic quotient (qCO2) decreased with T3 and W4 combinations. Kernel and system yield were 39.42% and 51.60% higher under T3 + W1 and T3 + IWM combinations, respectively. Talaromyces flavus was identified under T3 + IWM. The qCO2 was exhibited with significant negative correlation with all biological attributes, while yield did not correlate. This suggest qCO2 as potential indicator to assess agro-ecosystem. The PCA selected variables (enzymes, organic carbon, and microbial parameters) are highly supported by zero-till + residues, and can indicate improved soil health and sustained productivity.